ЕPIDEMIOLOGICAL AND СLINICAL FEATURES OF INFLUENZA IN CHILDREN IN THE STAVROPOL TERRITORY IN THE EPIDEMIC PERIOD OF 2015–2016 AND 2016–2017 YEARS - S. M. Bezrodnova; N. A. Yatsenko; O. O. Kravchenko; Sh. M. Khurtsilava (Журнал инфектологии)
Objective: to study the clinical and epidemiological features of influenza in children in the Stavropol Territory.Materials and methods: influenza prevalence is analyzed from 2015 to 2017 the paper used the data from the Territorial Rospotrebnadzor in the Stavropol Territory. We used the following methods: bibliographic, monographic description, epidemiological, analytical, statistical methods.Results: Among the deciphered acute respiratory viral infections, the specific gravity of influenza A (H1N1) 09 in 2016 reached 78%, and in 2017 influenza B prevailed – in 57,4% of children, and influenza A (H3N2) – in 42,6% of cases. In 2016 68,5% of children under 6 years of age, of all admitted, were hospitalized, and in 2017 – 83,86%. We presented the peculiarities of the course of influenza in different epidemic seasons.Conclusion: Unvaccinated children up to 6 years of age have the disease mainly in severe forms and with complications. The epidemic period began to increase in 2015–2016 at week 52, and in 2016–2017 from week 48, ended at week 13 and at week 17. At the epidemic of 2015–2016, intoxication syndrome with chills, microcirculation disturbance, catarrhal syndrome, ARDS prevailed in the clinical picture. The epidemic season of 2016–2017 was characterized by intoxication syndrome, encephalic reaction, hemorrhagic and myalgic syndromes.